Identifying which factors impact bowling and batting performances during the "death" phase of an innings in international men`s 50-over cricket - Jamil, M.; Kerruish, S.; Mehta, S.; Phatak, A.; Memmert, D.; McRobert, A. (International Journal of Performance Analysis in Sport, 2023)
In this study, 3,767 balls bowled by international-level fast bowlers across two One-Day International (ODI) tournaments were analysed to determine how to effectively bowl during the "death" phase of an innings (final 10 overs). The results of chi-squared analyses revealed that bowling length, bowling line, batter quality and having wickets in hand were all associated with the concession of runs during the death phase (all p < 0.001). Specifically, the yorker length is revealed to be very effective at restricting runs conceded, whereas the opposite is true for the half-volley and full-toss lengths. The batting side having five or more wickets in hand results in greater than expected runs being scored during the death phase. Furthermore, the results reveal that middle order batters score more runs than their tail-ender team-mates during this death phase, suggesting that middle-order batters have to assume the role of "finishers". From a practical perspective, the results of this study clearly identify areas bowlers can target to constrict the scoring of runs as well as areas they should avoid. Batting strategies in the death phase should consist maintaining five or more wickets in hand and thereby not exposing tail-enders to the bowling attack.